Synthesis of indanes via carbene-catalyzed single-electron-transfer processes and cascade reactions - Wang, Yuhuang (2020)
A carbene-catalyzed cascade reaction is developed for the synthesis of multi-substituted indane derivatives. The reaction involves two sequential Michael-addition steps, of which the first step is enabled by an NHC-mediated radical process. This work demonstrates the synthetic potentials of NHC-mediated single-electron-transfer processes for efficient reactions and rapid synthesis.